(untitled) (The Research of Medical Science Review, 2024)
To evaluate the level of awareness of mental health conditions among the different sociodemographic groups of Pakistan, To rule out the association of mental health conditions with the socio-demographic characteristics to find out the factors that affect communities, Mental health literacy defines as knowledge and attitude about mental health conditions which are low worldwide but specifically low in developing countries like Pakistan. Mental health conditions have also shown significant relationship with poverty and socioeconomic problems. And the most urgent problem of mental health care in Pakistan is the lack of personal and financial resources. This increases the barriers to seek help and contributes to the stigmatization of the mentally ill. This study aims to bring attention to this issue with the help of this survey, Study design: Cross-sectional study, In this study, around 400 students were included, either studying pre-medical in colleges or medical sciences in universities in all over Pakistan. An online survey was conducted, after their given consent. We estimated the level of awareness of the mental health conditions. We will have a deductive approach to this research, The demographic makeup of the total participants was 26% men and 74% women. As to educational attainment a considerably large population (63%) of participants’ highest level of education was bachelor and above, whereas 36.7% were primary education students with 0.3% of data missing. Socioeconomic conditions of the participants reflected that majority (about 59.9%) are financially unstable, or reported instability, while 13.5% occasional instability and 21.5% had financial stability with the data of 2.1% missing. One major occupation in the overall participants was students (88.3%) with 9.4% employed and 1.8% un-employed with .5% missing data, Majority of the participants reported single on their marital status (87.2%) with 12.2% married and only 5% of data missing. Most of the participants have their residence in Sindh (86.5%). With (13.5%) has their residence in Punjab, Mental illness has reached an appalling level in Pakistan, specifically effecting areas with “low literacy rates" and “low socio economic / income areas”. In Pakistan, its prevalence is estimated to be from 22% to 60%. Karachi city with an estimated population of 14.9 million is averaged to be at 47% of the total. The bio medical aspect of mental illness is largely ignored, and it leads to many stress inducing scenarios not being handled properly. And it destroys the health of the patient mentally as well as physically. To improve current treatment plans it is necessary to understand how mental illnesses are perceived by the public and that’s what ours. Research aims to deduce from the survey we have conducted.